Optimising Workplace Efficiency with Physical Activity Intervention - Hadl, Ivana (Digital Repository of Theses, 2024)
This research explored the relationship between physical activity, employee empowerment, and business productivity in the workplace. Productivity can be measured across various dimensions such as absenteeism, presenteeism, employee morale, or return on investment, but the presence of an employee doesn't equal a productive one. Considering factors like increased life expectancy and the intricacies that COVID-19 brings along, this study explored the significance of physical activity in enhancing motivation, especially intrinsic, as a main contributor to the overall well-being of employees, company performance, and health sustainability. Through an extensive theoretical framework based on psychology, kinesiology, and neuroscience of movement this research explains habit formation due to precisely chosen exercise and highlights the potential benefits of education and motivation in developing independence in being physically active. It explained the importance of improving health self-care awareness and emphasized prevention over treatment. Except individual framework of research, this study discussed societal and environmental implications of a sedentary lifestyle arguing for the workplace as an ideal setting for health risk assessment and health promotion activities. For this research mixed-methods design was used, which combines both quantitative and qualitative data collection methods. Through tailored functional movement exercise programs, walking sessions, and education about body movement, this study aims to explain that awakening and strengthening of inborn movement patterns could boost our cognitive functions such as creativity, concentration, focus, and memory and as such, impact employees' performance and productivity. The significance of the research lies in its potential to deliver evidence-based interventions for improving employees' health and overall well-being through physical activity, enhance employees' empowerment for higher organizational performance, and impact sustainability by reducing unnecessary healthcare costs related to non-communicable diseases. Additionally, this study underscored the role of healthcare professionals, particularly physiotherapists, in promoting movement as a means of preventive healthcare and sustainable workforce management. Ultimately, this research contributed to the development of integrated solutions for fostering a healthier and more productive workforce, with implications at both, local and global levels.